Processing instruction in helping map forms and meaning in second language acquisition of English simple past. Issue 6 (2nd November 2018) - Chan, Mable
ABSTRACT: In the first phase of this study, how English simple past is being taught in the classroom was examined through a questionnaire. The findings report how primary and secondary teachers perceived the difficulties faced by Cantonese English as a second language learners when acquiring English simple past, and the dominant teaching approaches or strategies used to address the problems. The second phase of the study examined the role of explicit instruction versus implicit instruction by involving primary 2 students being taught using three different forms of pedagogical intervention: processing instruction, traditional instruction, and implicit instruction. Findings show that the processing instruction group had significant improvement from pretest to posttest in the interpretation task, and they also obtained the greatest gains. In the production task, both processing instruction and traditional instruction groups obtained greatest gains and their improvement was significant. Explicit instruction was found to be more effective than implicit instruction in second language acquisition of English simple past.